Déjà vu [videorecording (DVD)] - Scott, Tony, 1944-2012; Washington, Denzel, 1954-; Kilmer, Val, 1959-; Patton, Paula (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
A ferry filled with crewmen from the USS Nimitz and their families is blown up in New Orleans during Mardi Gras. BATF Doug Carlin is brought in to assist in the recovery of evidence from the massive investigation, and gets attached to an experimental FBI surveillance unit. The unit uses technology to directly look back in time a little over four days into the past. While tracking down the bomber, Carlin gets an idea in his head: would it be possible to use the device to actually travel back in time and not only prevent the bombing but also the murder of a local woman whose truck was used in the bombing?